Case Report Tuberculous Spondylitis in Elderly with Polyneuropathy - Isabella Diah Ayu Laraswati; Lie Adityo Hansen (Berkala Ilmiah Kedokteran Duta Wacana, 2021)
Background Tuberculous (TB) spondylitis or Pott’s Disease is a manifestation of extrapulmonary tuberculosis infection caused by the hematogenous and lymphomatous spread of Mycobacterium Tuberculosis, causing infection in the vertebral bones. Approximately 10% of extrapulmonary TB cases are TB spondylitis. Pulmonary and extrapulmonary tuberculosis cases are considerable cases in developing countries. Indonesia is a country with the third-highest prevalence of TB in the world after China and India.Objective The aim of this study was to report a case of TB spondylitis in a 66 years old woman with polyneuropathy at Bethesda Hospital Yogyakarta.Case description A 66 years old female patient presented with complaints of pain and difficulty in moving the left lower limb 3 months ago. The patient had a history of hypertension 5 years ago, while the family history was not specific. The patient was generally in pain with full awareness and cooperation. Vital sign examination showed blood pressure 140/80 mmHg, pulse 82 beats per minute, and respiratory rate of 22 breaths per minute. The lumbosacral-MRI examination was performed without contrast material and L2-L5 TB Spondylitis, with L2-L3 Disc protrusion, was found.Conclusion Tuberculous spondylitis (TB) may cause paradiscal inflammation, edema, and progressive bone destruction due to lysis of anterior bone tissue and secondary ischemia which will lead to collapse. Pain, difficulty moving, and local swelling are the most common complaints. Abnormalities in the curvature, misalignment of the vertebrae, deformity and bone destruction might be found in MRI radiological imaging. Treatment of TB spondylitis prioritizes administering of anti-TB drugs combined with immobilization using a girdle. The prognosis for TB spondylitis varies depending on the clinical manifestations.